2010
DOI: 10.1002/j.0022-0337.2010.74.11.tb05001.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Senior Brazilian Dental Students About Mouth Preparation and Removable Partial Denture Design

Abstract: This study aimed to evaluate the knowledge of senior dental students about mouth preparation and removable partial denture (RPD) design. Two hundred sixty-six senior students from eleven dental schools in the State of São Paulo, Brazil, comprised the sample. The subjects examined two partially edentulous casts mounted on a semiadjustable articulator, answered a questionnaire regarding the treatment plan, and drew the RPD design. The casts consisted of Kennedy Class III, modiication 1 maxillary arch and Class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
(22 reference statements)
1
12
0
1
Order By: Relevance
“…It is possible that dentists put a greater emphasis on CC-RPD instructions than A-RPD instructions because of the high cost of CC-RPDs, or because CC-RPDs were prescribed by dentists who possessed greater skills than those who prescribed A-RPDs. The results of this research showed that most of the design components for A- and CC-RPDs were not clearly prescribed, which again is similar to previous studies ( 13 , 17 , 23 , 24 ). This again indicates that dentists leave it mainly to technicians to design the prosthesis, which is unacceptable as the dentists should be fully responsible for the RPD design, since they perform the examination, diagnosis, and treatment planning.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is possible that dentists put a greater emphasis on CC-RPD instructions than A-RPD instructions because of the high cost of CC-RPDs, or because CC-RPDs were prescribed by dentists who possessed greater skills than those who prescribed A-RPDs. The results of this research showed that most of the design components for A- and CC-RPDs were not clearly prescribed, which again is similar to previous studies ( 13 , 17 , 23 , 24 ). This again indicates that dentists leave it mainly to technicians to design the prosthesis, which is unacceptable as the dentists should be fully responsible for the RPD design, since they perform the examination, diagnosis, and treatment planning.…”
Section: Discussionsupporting
confidence: 88%
“…Alternatively, it could be due to weak undergraduate training in writing laboratory instructions and designing RPDs. Less than a quarter of A-RPD and less than half of CC-RPD cases came with written instructions, more than those found by Neto et al ( 23 ).…”
Section: Discussionmentioning
confidence: 63%
“…well planned removable partial denture (RPD) restores oral functions, esthetics and imparts minimum stress to the hard and soft tissues of oral cavity. 1 Poorly designed removable partial dentures may result in periodontal bone loss, caries, gingivitis, periodontal damage and stomatitis of supporting tissues. 2,3,4 Acquisition of skill of partial denture design is crucial to its successful implementation during clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4 Acquisition of skill of partial denture design is crucial to its successful implementation during clinical practice. 1 Many designs proposed in literature are without sufficient scientific evidence. 5 Worldwide studies have shown disagreements over removable partial denture designs as well as lack of communication skills of dentists, pertaining to details of removable partial denture design to dental laboratories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation